Management of Masjidku Makmur Program at Yayasan Masjid Nusantara Bandung - Imron Rosidi; Anjas Ardana (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This research is motivated by the management of the mosque, which the Nusantara Mosque Foundation carries out. The Nusantara Mosque Foundation chose to focus on building civilization through the mosque through the My Mosque Prosperous Program. This study aims to find out how the Bandung Nusantara Mosque Foundation manages the Masjidku Makmur program. This study uses a qualitative method. The results showed that the management of the Masjidku Makmur program carried out by the Masjid Nusantara Bandung Foundation cannot be separated from the four management functions, better known as Planning, Organizing, Actuating, and Controlling (POAC). This article finds that the Nusantara Mosque Foundation has four programs or activities to prosper mosques. The four activities or programs are mosque management training, funeral management training, Nusantara mosque bulletins, and Hari Raya Allowances (THR) to marbots and mosque imams.